Evaluation of coal combustion residuals in cement systems - Ashish D. Patel; Jordan K. Magnuson; Timothy G. Townsend; Christopher C. Ferraro (Journal of Hazardous Materials, 2026)

Optimization of pretreatments for municipal solid waste incineration ash reuse in cement manufacture: A critical review - Jordan K. Magnuson; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2026)

Environmental analysis of a ten-year pilot project using municipal solid waste incinerator bottom ash as road base: a case study - Jordan K. Magnuson; Kate D. Weiksnar; Steven J. Laux; Justin G. Roessler; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2026)

Celestial hazards: immunological and pulmonary effects of lunar and Martian regolith simulants - Christopher C. Ferraro; Deyaneira Tirado; Mariola J. Ferraro (Life Sciences in Space Research, 2025)

Evaluation of alkali-silica reactivity behavior and mitigation in waste-to-energy bottom ash for sustainable aggregate use in concrete - Kate D. Weiksnar; Jordan K. Magnuson; Ashish D. Patel; Robbie Posada; Christopher C. Ferraro; Timothy G. Townsend (Waste Management, 2025)

A review of the suitability and performance of phosphogypsum as a material for road base and subbase construction - Malik A. DeWindt; Kate D. Weiksnar; Steven J. Laux; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2025)

Impacts of advanced metals recovery on municipal solid waste incineration bottom ash: aggregate characteristics and performance in portland limestone cement concrete - Kate D. Weiksnar; Ethan J. Marks; Margaret J. Deaderick; Isabella Meija-Ruiz; Christopher C. Ferraro; Timothy G. Townsend (Waste Management, 2024)

Processing municipal solid waste incineration bottom ash for integration into cement product manufacture - Jordan K. Magnuson; Kate D. Weiksnar; Ashish D. Patel; Kyle A. Clavier; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2023)

Assimilation of Blended Satellite Soil Moisture Data Products to Further Improve Noah-MP Model Skills - Jifu Yin; Xiwu Zhan; Michael Barlage; Sujay Kumar; Andrew Fox; Clement Albergel; Christopher R. Hain; Ralph R. Ferraro; Jicheng Liu (Journal of Hydrology, 2023)

An Experimental Platform to Study Wind, Hydrodynamic, and Biochemical Conditions in the Littoral Zone During Extreme Coastal Storms - Brian Phillips; Forrest Masters; Britt Raubenheimer; Maitane Olabarrieta; Elise Morrison; Pedro Fernández-Cabán; Christopher Ferraro; Justin Davis; Taylor Rawlinson; Michael Rodgers (Oceanography, 2023)
Tropical cyclones and other extreme coastal storms cause widespread interruption and damage to meteorological and hydrological measurement stations exactly when researchers need them most. There is a longstanding need to collect collocated and synchronized measurements in areas where storms severely damage civil/coastal infrastructure. To fill this observational gap, researchers led by author Masters developed a state-of-the-art monitoring station called a “Sentinel.” Sentinels are intended for temporary installation on the beach between the mean tidal datum and the sand dunes and are engineered to operate in and measure extreme wind, storm surge, wave, and hazardous water quality conditions. They are envisioned as a shared-use resource—a hardened IoT (Internet of Things) platform set up in the right place at the right time to study wind and wave loads, coastal erosion and morphology changes, water quality, and other processes during extreme coastal storms.

Cold-bonding process for treatment and reuse of waste materials: Technical designs and applications of pelletized products - Alberto Ferraro; Francesco Colangelo; Ilenia Farina; Marco Race; Raffaele Cioffi; Christopher Cheeseman; Massimiliano Fabbricino (Critical Reviews in Environmental Science and Technology, 2021)

The long and narrow path for novel cell‐based seafood to reduce fishing pressure for marine ecosystem recovery - Benjamin S. Halpern; Jason Maier; Heather J. Lahr; Gordon Blasco; Christopher Costello; Richard S. Cottrell; Olivier Deschenes; Danielle M. Ferraro; Halley E. Froehlich; Gavin G. McDonald; Katherine D. Millage; Michael J. Weir (Fish and Fisheries, 2021)
Cell‐based seafood is an emerging novel food, with many start‐up companies aspiring for ocean conservation benefits through expanded market share that displaces wild‐caught seafood. However, the ability for cell‐based seafood to achieve this conservation outcome is often oversimplified and will rely on an extensive, and we find somewhat tenuous, chain of events. Here, we outline the technological, behavioural, market and ecological changes that must occur along this pathway, and conclude that fisheries recoveries and collateral ocean benefits are unlikely to result from cell‐based seafood technology. In particular, we detail nine necessary steps and argue that failure at any one step could hinder or even eliminate cell‐based seafood's conservation effects. We additionally draw comparisons to aquaculture and share broader lessons for other demand‐driven product interventions.